Two-component developer and image formation device
The two-component developer addresses the issue of fog in electrophotography by using strontium titanate particles with specific diameters and content ratios in both carrier and toner particles, enhancing charge stability and transfer efficiency.
Patent Information
- Application Number
- JP2023161473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
Existing two-component developers for electrophotography fail to adequately suppress the occurrence of fog, despite the use of additives in the toner and carrier.
A two-component developer comprising carrier particles with a carrier matrix and strontium titanate particles, and toner particles with strontium titanate external additives, where the strontium titanate particles have specific primary particle diameters and content ratios to optimize charge transfer and retention.
The developer effectively suppresses the occurrence of fog by stabilizing the charge amount of toner particles and promoting smooth charge transfer between carrier and toner particles, even during extended printing operations.
Smart Images

Figure 2025052656000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a two-component developer and an image forming apparatus. [Background technology]
[0002] In the electrophotographic method, for example, a two-component developer including a carrier containing carrier particles and a toner containing toner particles is used. The two-component developer is required to be able to suppress the occurrence of fogging.
[0003] In response to such demands, for example, it has been proposed to use a carrier for electrophotographic developer in which a carrier core material is coated with a resin layer, and in which at least one type of additive used in the toner has been added and mixed in advance in a process prior to mixing with the toner (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-91878 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, even the two-component developer using the carrier described in Patent Document 1 cannot sufficiently suppress the occurrence of fogging.
[0006] SUMMARY OF THE PRESENT EMBODIMENT In view of the above problems, an object of the present invention is to provide a two-component developer capable of suppressing the occurrence of fogging, and an image forming apparatus using the two-component developer. [Means for solving the problem]
[0007] The two-component developer of the present invention includes a carrier including carrier particles and a toner including toner particles. The carrier particles include carrier base particles and first strontium titanate particles attached to the surface of the carrier base particles. The carrier base particles include a carrier core and a coating layer that covers the carrier core. The coating layer contains a coating resin and barium titanate particles. The coating resin contains a silicone resin. The toner particles include toner base particles and an external additive that adheres to the surface of the toner base particles. The external additive contains second strontium titanate particles. The first strontium titanate particles and the second strontium titanate particles each have a number average primary particle diameter of 15 nm or more and 85 nm or less. The difference between the number average primary particle diameters of the first strontium titanate particles and the second strontium titanate particles is 10 nm or less. The content of the second strontium titanate particles relative to 100.0 parts by mass of the toner base particles is 0.3 parts by mass or more and 0.9 parts by mass or less. The content of the barium titanate particles relative to 100 parts by mass of the coating resin is 2 parts by mass or more and 47 parts by mass or less. The content of the first strontium titanate particles relative to 100.00 parts by mass of the carrier base particles is 0.02 parts by mass or more and 0.06 parts by mass or less. When a printing test was conducted in which a pattern image with a print rate of 1% was intermittently printed one sheet at a time on A4-sized printing paper, the two-component developer of the present invention had a print rate of 100% at a time t1 immediately after the first sheet was printed and a time t2 immediately after the 100th sheet was printed. 100 , and the time t immediately after printing the 1000th sheet 1000 At any time point, the ratio (N / L) of the desorption rate N of the strontium titanate particles to the desorption rate L of the strontium titanate particles satisfies the following formula (1). 1.1≦N / L≦6.5 (1)
[0008] The detachment rate N is calculated as N=100×(P1-Q1) / P1, where P1 is the content of the first strontium titanate particles in the carrier particles before the printing test, and Q1 is the content of the first strontium titanate particles immediately after a predetermined number of sheets are printed. The detachment rate L is calculated as L=100×(P2-Q2) / P2, where P2 is the content of the second strontium titanate particles in the toner particles before the printing test, and Q2 is the content of the second strontium titanate particles immediately after a predetermined number of sheets are printed.
[0009] The image forming apparatus of the present invention includes the above-mentioned two-component developer, a photoconductor, a charging device for charging the surface of the photoconductor, and a developing device for supplying the toner to the surface of the photoconductor and developing it into a toner image. The printing durability test is performed using the image forming apparatus. Effect of the Invention
[0010] The two-component developer and image forming apparatus of the present invention can suppress the occurrence of fogging. [Brief description of the drawings]
[0011] [Figure 1] 3A and 3B are diagrams illustrating an example of carrier particles and toner particles included in a two-component developer according to a first embodiment. [Diagram 2] FIG. 13 illustrates an example of an image forming apparatus according to a second embodiment. [Diagram 3] 3 is a diagram showing a developing device and its surroundings provided in the image forming apparatus in FIG. 2; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] A preferred embodiment of the present invention will be described below. The carrier is an aggregate (e.g., powder) of carrier particles. The toner is an aggregate (e.g., powder) of toner particles. The external additive (silica particles and spacer particles) is an aggregate (e.g., powder) of external additive particles. Unless otherwise specified, the evaluation results (values indicating shape, physical properties, etc.) of the powder (more specifically, the powder of toner particles, the powder of external additive particles, the magnetic powder, the powder of carrier particles, etc.) are the number average of values measured for each of a considerable number of particles selected from the powder.
[0013] Volume median diameter of powder (D 50 ) is a value measured using a laser diffraction / scattering type particle size distribution analyzer (for example, "LA-950" manufactured by Horiba, Ltd.) unless otherwise specified.
[0014] Unless otherwise specified, the number average primary particle diameter of a powder is the number average value of the circle equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) measured using a scanning electron microscope. The number average primary particle diameter of a powder is, for example, the number average value of the circle equivalent diameters of 100 primary particles. The number average primary particle diameter of particles refers to the number average primary particle diameter of particles in the powder unless otherwise specified.
[0015] Unless otherwise specified, the chargeability refers to the chargeability in triboelectric charging. For example, a standard carrier (standard carrier for negatively charged toner: N-01, standard carrier for positively charged toner: P-01) provided by the Imaging Society of Japan is mixed with the measurement target (e.g., toner) and stirred to triboelectrically charge the measurement target. The charge amount of the measurement target is measured before and after triboelectric charging, for example, with a small suction-type charge amount measuring device (Trek's "MODEL 212HS"), and the greater the change in charge amount before and after triboelectric charging, the stronger the chargeability of the measurement target.
[0016] Unless otherwise specified, the "major component" of a material means the component that is contained in the largest amount in the material on a mass basis.
[0017] The glass transition point (Tg) and melting point (Mp) are values measured according to JIS (Japanese Industrial Standards) K7121-2012 using a differential scanning calorimeter (Seiko Instruments Inc.'s "DSC-6220") unless otherwise specified. In the endothermic curve of a sample measured with a differential scanning calorimeter (vertical axis: heat flow (DSC signal), horizontal axis: temperature), the temperature of the inflection point due to glass transition is the glass transition point (Tg). In detail, the temperature of the inflection point due to glass transition is the temperature of the intersection between the extrapolated line of the baseline and the extrapolated line of the falling line. The temperature of the maximum endothermic peak in the endothermic curve is the melting point (Mp). The softening point (Tm) is a value measured using a high-temperature flow tester (Shimadzu Corporation's "CFT-500D") unless otherwise specified. In the S-shaped curve (horizontal axis: temperature, vertical axis: stroke) of a sample measured with a high-speed flow tester, the temperature at which "(baseline stroke value + maximum stroke value) / 2" is the softening point (Tm).
[0018] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the polymer name is expressed by adding "based" after the compound name, it means that the repeating unit of the polymer is derived from the compound or its derivative. Acrylic and methacrylic may be collectively referred to as "(meth)acrylic". Each component described below may be used alone or in combination of two or more types, unless otherwise specified.
[0019] <First embodiment: Two-component developer> The first embodiment of the present invention relates to a two-component developer (hereinafter, sometimes simply referred to as a developer). The developer of this embodiment includes a carrier including carrier particles and a toner including toner particles. The carrier particles include carrier base particles and first strontium titanate particles adhering to the surfaces of the carrier base particles. The carrier base particles include a carrier core and a coating layer that covers the carrier core. The coating layer contains a coating resin and barium titanate particles. The coating resin contains a silicone resin. The toner particles include toner base particles and an external additive that adheres to the surfaces of the toner base particles. The external additive contains second strontium titanate particles. The first strontium titanate particles and the second strontium titanate particles each have a number average primary particle diameter of 15 nm or more and 85 nm or less. The difference between the number average primary particle diameters of the first strontium titanate particles and the second strontium titanate particles is 10 nm or less. The content of the strontium titanate particles relative to 100.0 parts by mass of the toner base particles is 0.3 parts by mass or more and 0.9 parts by mass or less. The content of the barium titanate particles relative to 100 parts by mass of the coating resin is 2 parts by mass or more and 47 parts by mass or less. The content of the strontium titanate particles relative to 100.00 parts by mass of the carrier base particles is 0.02 parts by mass or more and 0.06 parts by mass or less. When a printing test was conducted in which a pattern image with a printing rate of 1% was intermittently printed one sheet at a time on A4-sized printing paper, the developer of the present invention showed a high printing efficiency at time t1 immediately after the first sheet was printed and at time t2 immediately after the 100th sheet was printed. 100 , and the time t immediately after printing the 1000th sheet 1000 At any time point, the ratio (N / L) of the desorption rate N of the strontium titanate particles to the desorption rate L of the strontium titanate particles satisfies the following formula (1). 1.1≦N / L≦6.5 (1)
[0020] The detachment rate N is calculated as N=100×(P1-Q1) / P1, where P1 is the content of the strontium titanate particles in the carrier particles before the printing test, and Q1 is the content of the strontium titanate particles immediately after a predetermined number of sheets have been printed. The detachment rate L is calculated as L=100×(P2-Q2) / P2, where P2 is the content of the strontium titanate particles in the toner particles before the printing test, and Q2 is the content of the strontium titanate particles immediately after a predetermined number of sheets have been printed.
[0021] In the developer of the present embodiment, the toner is charged by, for example, stirring the carrier and the toner in the developing device. The developer of the present embodiment is suitable for an image forming device of a so-called trickle development type described later in the second embodiment. In particular, the developer of the present embodiment is suitable as an initial developer used in an image forming device of a trickle development type. After starting development of an electrostatic latent image with the initial developer in the developing device, the image forming device of the trickle development type develops the electrostatic latent image with the developer in the developing device while discharging the developer in the developing device and replenishing the replenishing developer into the developing device. During image formation, the carrier is also replenished into the developing device together with the toner, and the carrier in the developing device is discharged in an amount that is excessive due to the replenishment, thereby suppressing deterioration of the carrier in the developing device. In addition, suppressing deterioration of the carrier can reduce the number of times the carrier in the developing device is replaced. The developer of the present embodiment may be used as a developer (hereinafter, may be described as a general developer) for an image forming device that does not use the trickle development type.
[0022] In a general developer (or initial developer), the toner ratio (100×toner mass / carrier mass), which indicates the ratio of the toner mass to the carrier mass, is preferably 1% to 20%, and more preferably 5% to 15%. In a refill developer, the carrier ratio (100×carrier mass / toner mass), which indicates the ratio of the carrier mass to the toner mass, is preferably 2% to 30%, and more preferably 5% to 20%.
[0023] The developer of the present embodiment has the above-mentioned configuration, and thus can suppress the occurrence of fogging. The reason for this is explained below. The carrier of the developer of the present embodiment contains an appropriate amount of barium titanate particles in the coating layer of the carrier particles. Barium titanate particles are ferroelectric and have a high relative dielectric constant. Therefore, carrier particles containing barium titanate particles in the coating layer have a high charge retention ability. Carrier particles with a high charge retention ability can continue to impart a sufficient amount of charge to the toner particles by contacting with the toner particles. Furthermore, since the toner particles contain second strontium titanate particles as an external additive, charge transfer is promoted and the charge amount rises quickly. As a result, the developer of the present embodiment can stabilize the charge amount of the toner particles, and thus the occurrence of fogging can be suppressed.
[0024] Furthermore, when an image is formed using a known developer, a low-charged replenishment toner is replenished to a toner that is already highly charged and exists in a developing device of an image forming apparatus. In this case, in the case of a known developer, the charge of the replenishment toner remains low, and the toner may scatter. This phenomenon occurs significantly when the toner particles of the known developer contain a titanic acid compound. This is because a toner containing a titanic acid compound can hold a large amount of charge (has a high electrostatic capacity), and therefore takes more time to reach a saturated charge amount. In particular, in a low-humidity environment, there is less moisture that contributes to charge transfer between the carrier particles and the toner particles, and therefore the time required for the toner to reach a saturated charge amount increases further. In contrast, the developer of this embodiment contains first strontium titanate particles as carrier particles. The first strontium titanate particles can remove charge from the toner in the developing device and suppress the charge-up of the toner in the developing device. Therefore, in the case of image formation using the developer of this embodiment, charge transfer between the toner in the developing device and the replenishment toner becomes smooth, and the charge amount of the replenishment toner is easily increased. As a result, the developer of this embodiment can more effectively suppress the occurrence of fogging.
[0025] Here, when the first strontium titanate particles are detached from the carrier particles, the effect of suppressing the occurrence of the above-mentioned fogging is reduced. On the other hand, in the developer of this embodiment, as the toner is consumed in image formation, the second strontium titanate particles adhering to the toner particles gradually transfer to the carrier particles. When an excessive amount of the second strontium titanate particles is attached to the carrier particles, it becomes difficult for the carrier particles to charge the toner particles. Therefore, in the developer of this embodiment, the ratio (N / L) of the detachment rate N of the first strontium titanate particles to the detachment rate L of the second strontium titanate particles is set within a predetermined range, so that the occurrence of fogging can be more effectively suppressed.
[0026] The carrier includes carrier particles. The toner includes toner particles. An example of the carrier particles and toner particles contained in the developer of this embodiment will be shown below with reference to FIG. 1. FIG. 1 shows carrier particles 1, which are an example of the carrier particles contained in the developer of this embodiment, and toner particles 4, which are an example of the toner particles contained in the developer of this embodiment. The carrier particles 1 include carrier base particles 2 and first strontium titanate particles 3. The first strontium titanate particles 3 are attached (provided) on the surface of the carrier base particles 2. The carrier base particles 2 include a carrier core 2a and a coating layer 2b. The coating layer 2b covers the entire surface of the carrier core 2a.
[0027] The toner particles 4 include toner base particles 5 and external additives 6. The toner base particles 5 are non-capsulated toner base particles. The external additives 6 are attached (provided) on the surfaces of the toner base particles 5. The external additives 6 include strontium titanate particles 6a, base silica particles 6b, and spacer particles 6c.
[0028] An example of the carrier particles and toner particles contained in the developer of this embodiment has been described above with reference to FIG. 1. However, in the developer of this embodiment, the structures of the carrier particles and toner particles are not limited to those shown in FIG. 1. For example, the toner base particles may be capsule toner base particles including a toner core and a shell layer covering the toner core. The external additive may not include base silica particles and spacer particles. The coat layer of the carrier particles may cover at least a part of the carrier core. That is, a part of the carrier core may be exposed.
[0029] The developer of this embodiment was used in a printing test at time t1, time t 100 , and time t 1000 At any time point, it is preferable that the ratio (N / L) of the desorption rate N of the strontium titanate particles to the desorption rate L of the strontium titanate particles satisfies the following formula (1a). 1.6≦N / L≦4.8 (1a)
[0030] During a printing test, the developer of this embodiment preferably has a ratio (N / L) of 1.5 or more and 3.0 or less, and more preferably 1.8 or more and 2.5 or less, at time t1.
[0031] During the printing test, the developer of this embodiment 100 In the above, the ratio (N / L) is preferably 2.5 or more and 6.0 or less, and more preferably 3.5 or more and 4.5 or less.
[0032] During the printing test, the developer of this embodiment 1000 In the above, the ratio (N / L) is preferably 3.0 or more and 5.0 or less, and more preferably 3.5 or more and 4.5 or less.
[0033] In the developer of this embodiment, during a printing test, at time t1, the detachment rate L is preferably 1% or more and 10% or less, and more preferably 2% or more and 6% or less. In the developer of this embodiment, during a printing test, at time t1, the detachment rate N is preferably 4% or more and 16% or less, and more preferably 6% or more and 10% or less.
[0034] During the printing test, the developer of this embodiment 100 In the printing test, the desorption rate L is preferably 4% or more and 15% or less, and more preferably 6% or more and 10% or less. 100 In the above, the desorption rate N is preferably 25% or more and 45% or less, and more preferably 30% or more and 40% or less.
[0035] During the printing test, the developer of this embodiment 1000 In the printing test, the desorption rate L is preferably 10% or more and 30% or less, and more preferably 15% or more and 20% or less. 1000 In the above, the desorption rate N is preferably 40% or more and 80% or less, and more preferably 55% or more and 65% or less.
[0036] The desorption rate L and the desorption rate N can be measured by the method described in the Examples or a method based thereon.
[0037] [Carrier particles] The carrier particles include carrier base particles and strontium titanate particles attached to the surfaces of the carrier base particles.
[0038] (Carrier mother particles) The carrier base particle includes a carrier core and a coating layer that covers the surface of the carrier core.
[0039] (Career Core) The carrier core preferably contains a magnetic material. The carrier core may be a particle of a magnetic material, or may be a particle including a carrier core binder resin and particles of a magnetic material dispersed in the carrier core binder resin (hereinafter, may be referred to as a resin carrier core).
[0040] Examples of the magnetic material contained in the carrier core include ferromagnetic metals (more specifically, for example, iron, cobalt, nickel, and alloys containing one or more of these metals) and ferromagnetic metal oxides. Examples of the ferromagnetic metal oxide include ferrite and magnetite, which is a type of spinel ferrite. Examples of the ferrite include Ba ferrite, Mn ferrite, Mn-Zn ferrite, Ni-Zn ferrite, Mn-Mg ferrite, Ca-Mg ferrite, Li ferrite, Cu-Zn ferrite, and Mn-Mg-Sr ferrite. Examples of the method for producing the carrier core include a method including a process of crushing and firing a magnetic material. In the production of the carrier core, the saturation magnetization of the carrier can be adjusted by changing the amount of magnetic material added (particularly the ratio of the ferromagnetic material). In the production of the carrier core, the circularity of the carrier core can be adjusted by changing the firing temperature. In addition, the carrier core may be a commercially available product.
[0041] Examples of magnetic material particles used as carrier cores include ferrite particles. Ferrite particles tend to have sufficient magnetism for image formation using a two-component developer. Ferrite particles manufactured by a general manufacturing method tend not to be perfectly spherical and tend to have moderate irregularities on the surface. When the carrier core is a ferrite particle (ferrite core), from the viewpoint of improving the adhesion between the surface of the ferrite core and the coating layer, the arithmetic mean roughness of the surface of the ferrite core (more specifically, the arithmetic mean roughness Ra defined in JIS (Japanese Industrial Standards) B0601:2013) is preferably 0.3 μm or more and 2.0 μm or less.
[0042] The binder resin in the resin carrier core is preferably a polyester resin, a urethane resin, or a phenol resin, and more preferably a phenol resin. The magnetic material particles in the resin carrier core include, for example, particles containing one or more of the magnetic materials exemplified in the magnetic material.
[0043] In the carrier particles, the mass ratio of the carrier core to the total mass of the carrier core and the coating layer is preferably from 80% by mass to 99% by mass, and more preferably from 95% by mass to 99% by mass.
[0044] The number-average primary particle diameter of the carrier core is preferably 15 μm or more and 60 μm or less, and more preferably 15 μm or more and 30 μm or less. By making the number-average primary particle diameter of the carrier core 15 μm or more, the occurrence of carrier development can be suppressed. By making the number-average primary particle diameter of the carrier core 60 μm or less, the developability can be optimized.
[0045] The saturation magnetization of the carrier core in an applied magnetic field of 3000 Oe is preferably 60 emu / g or more and 80 emu / g or less. By setting the saturation magnetization of the carrier core to 60 emu / g or more, the occurrence of carrier development can be suppressed. By setting the saturation magnetization of the carrier core to 80 emu / g or less, the developability can be optimized.
[0046] (Coat layer) The coating layer contains a coating resin and barium titanate particles. The coating layer preferably further contains carbon black. The thickness of the coating layer is, for example, 0.3 μm or more and 2.0 μm or less.
[0047] The mass of the coating layer relative to 100.0 parts by mass of the carrier core is preferably 0.5 parts by mass or more and 10.0 parts by mass or less, more preferably 1.0 parts by mass or more and 3.0 parts by mass or less. By making the mass of the coating layer 0.5 parts by mass or more, the exposure of the carrier core can be suppressed. By making the mass of the coating layer 5.0 parts by mass or less, the carrier can easily charge the toner.
[0048] The coating resin includes a silicone resin. The content of the coating resin in the coating layer is preferably 50.0% by mass or more and 90.0% by mass or less, and more preferably 70.0% by mass or more and 85.0% by mass or less. The content of the silicone resin in the coating resin is preferably 90% by mass or more, and more preferably 100% by mass.
[0049] (Silicone resin) Silicone resin is a resin having a polysiloxane structure (e.g., an alkyl polysiloxane structure). Examples of silicone resins include silicone resins having a methyl group and epoxy resin-modified silicone resins. Examples of silicone resins having a methyl group include silicone resins having a methyl group and no phenyl group (hereinafter sometimes referred to as "methyl silicone resins"), and silicone resins having a methyl group and a phenyl group (hereinafter sometimes referred to as "methyl phenyl silicone resins"). As the silicone resin, methyl silicone resins are preferred.
[0050] (Barium titanate particles) By including the barium titanate particles in the coating layer, the carrier can easily impart a desired charge amount to the toner. In addition, by including the barium titanate particles in the coating layer, the strength of the coating layer can be optimized, and the strontium titanate particles can be prevented from being embedded in the coating layer.
[0051] The number-average primary particle diameter of the barium titanate particles is preferably 100 nm or more and 500 nm or less, more preferably 250 nm or more and 350 nm or less. Barium titanate particles having a number-average primary particle diameter of less than 100 nm tend to have a low relative dielectric constant. By making the number-average primary particle diameter of the barium titanate particles 100 nm or more, the carrier can more easily impart a desired charge amount to the toner. By making the number-average primary particle diameter of the barium titanate particles 500 nm or less, the barium titanate particles can be prevented from detaching from the coating layer.
[0052] In the coating layer, the content of the barium titanate particles relative to 100 parts by weight of the coating resin is 2 parts by weight to 47 parts by weight, preferably 10 parts by weight to 40 parts by weight, and more preferably 15 parts by weight to 25 parts by weight. By setting the content of the barium titanate particles to 2 parts by weight to 47 parts by weight, the electrostatic capacity of the carrier particles can be optimized. As a result, the developer of this embodiment can suppress the occurrence of fogging.
[0053] (Carbon Black) Carbon black promotes the migration of charges in the coating layer, making it easier for the carrier to impart a desired amount of charge to the toner.
[0054] The number-average primary particle diameter of the carbon black is preferably 10 nm or more and 200 nm or less, more preferably 20 nm or more and 60 nm or less. By making the number-average primary particle diameter of the carbon black 10 nm or more, the carrier can more easily impart a desired charge amount to the toner. By making the number-average primary particle diameter of the carbon black 200 nm or less, it is possible to suppress the carbon black from being detached from the coating layer.
[0055] In the coating layer, the content of carbon black relative to 100 parts by mass of the coating resin is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 5 parts by mass or more and 12 parts by mass or less. By making the content of carbon black 3 parts by mass or more, the carrier can more easily impart a desired charge amount to the toner. By making the content of carbon black 20 parts by mass or less, it is possible to suppress the carbon black from being detached from the coating layer.
[0056] (Other ingredients) The coating layer may further contain other components in addition to the coating resin, the barium titanate particles, and the carbon black, such as a charge control agent, an adhesion improver, and a crosslinking agent.
[0057] (Strontium titanate particles) The first strontium titanate particles may be doped. When the first strontium titanate particles are doped, the amount of the doped element may be 1.00 mass% or less, 0.10 mass% or less, or less than 0.01 mass% based on the total mass of the first strontium titanate particles. However, the first strontium titanate particles may not be doped. As the first strontium titanate particles, non-doped strontium titanate particles are preferred.
[0058] The content of the first strontium titanate particles relative to 100.00 parts by mass of the carrier base particles is 0.02 parts by mass or more and 0.06 parts by mass or less, and preferably 0.03 parts by mass or more and 0.05 parts by mass or less. By making the content of the first strontium titanate particles 0.02 parts by mass or more, the charge rise property of the replenishment toner can be optimized. By making the content of the first strontium titanate particles 0.06 parts by mass or less, the carrier base particles and the toner particles can easily come into contact with each other, and the toner can be sufficiently charged.
[0059] (Carrier Manufacturing Method) The method for producing the carrier includes, for example, a step of forming carrier base particles and a step of adding an external additive to the carrier base particles.
[0060] (Carrier mother particle formation process) In this step, a coating liquid is applied to the surface of the carrier core. The coating liquid contains a coating resin, barium titanate particles, a solvent, and an optional component (e.g., carbon black) that is used as needed. The solid content concentration of the coating liquid is preferably 10% by mass or more and 30% by mass or less.
[0061] Examples of the solvent for the coating liquid include lactam compounds (e.g., 2-pyrrolidone and N-methyl-2-pyrrolidone), ketone compounds (e.g., methyl ethyl ketone and methyl isobutyl ketone), cyclic ether compounds (e.g., tetrahydrofuran and tetrahydropyran), alcohol compounds (e.g., normal butanol and isobutanol), ester solvents (e.g., ethyl acetate and isobutyl acetate), and aromatic hydrocarbon compounds (e.g., toluene and xylene).Toluene is preferred as the solvent for the coating liquid.
[0062] Examples of methods for applying the coating liquid to the surface of the carrier core include a method of immersing the carrier core in the coating liquid and a method of spraying the coating liquid onto the carrier core in the fluidized bed. In the method of immersing the carrier core in the coating liquid, a small amount of the coating liquid is applied to the convex parts of the surface of the carrier core, while a large amount of the coating liquid is applied to the concave parts of the surface of the carrier core, so the amount of the coating liquid tends to be uneven. In contrast, in the method of spraying the coating liquid onto the carrier core in the fluidized bed, the coating liquid tends to be applied uniformly to both the convex parts and the concave parts of the surface of the carrier core. From the above, the method of spraying the coating liquid onto the carrier core in the fluidized bed is preferred as the method for applying the coating liquid onto the surface of the carrier core.
[0063] In this process, the carrier cores after the coating process are heated to remove the solvent contained in the coating liquid. If the coating liquid contains an uncured coating resin, the uncured coating resin is thermally cured. As a result, a coating layer is formed from the coating liquid. The heating temperature during heating is preferably 100°C or higher and 300°C or lower, more preferably 180°C or higher and 220°C or lower. The heating time during heating is preferably 30 minutes or higher and 90 minutes or lower, more preferably 50 minutes or higher and 70 minutes or lower.
[0064] (External addition process to carrier base particles) In this step, for example, a mixer is used to mix the carrier base particles and the strontium titanate particles. By mixing, the strontium titanate particles are attached to the surface of the carrier base particles, and a carrier containing carrier particles is obtained. The mixing in the external addition step to the carrier base particles is preferably carried out under conditions in which the strontium titanate particles are not completely embedded in the carrier base particles. When the external addition step is carried out using a rocking mixer (registered trademark), the mixing time is preferably 4.0 minutes or more and 25.0 minutes or less, more preferably 12.0 minutes or more and 18.0 minutes or less.
[0065] [Toner particles] The toner particles include toner base particles and an external additive that adheres to the surface of the toner base particles.
[0066] (External additives) The external additive adheres to the surface of the toner base particle. The external additive includes strontium titanate particles. The external additive preferably further includes spacer particles and base silica particles. The external additive may further include particles other than the strontium titanate particles, the spacer particles, and the base silica particles (hereinafter, other external additive particles). The total content of the strontium titanate particles, the spacer particles, and the base silica particles in the external additive is preferably 60% by mass or more and 90% by mass or less.
[0067] (Strontium titanate particles) The composition of the strontium titanate particles can be the same as that of the strontium titanate particles. The number average primary particle diameter of the strontium titanate particles and the strontium titanate particles is 15 nm or more and 85 nm or less, and preferably 25 nm or more and 40 nm or less. By making the number average primary particle diameter of the strontium titanate particles and the strontium titanate particles 15 nm or more, respectively, the transfer of charge between the toner particles and the carrier particles can be promoted. By making the number average primary particle diameter of the strontium titanate particles 85 nm or less, the strontium titanate particles can be prevented from being extremely easily detached from the coating layer. By making the number average primary particle diameter of the strontium titanate particles 85 nm or less, the strontium titanate particles can be prevented from being extremely easily detached from the toner mother particles.
[0068] The difference in number-average primary particle size between the strontium first titanate particles and the strontium second titanate particles is 10 nm or less, preferably 1 nm or less, and more preferably 0 nm. By reducing the difference in number-average primary particle size between the strontium first titanate particles and the strontium second titanate particles, it becomes easier to adjust the ratio (N / L) to the above-mentioned range.
[0069] The content of the strontium titanate particles relative to 100.0 parts by mass of the toner base particles is 0.3 parts by mass or more and 0.9 parts by mass or less, and preferably 0.4 parts by mass or more and 0.6 parts by mass or less. By making the content of the strontium titanate particles 0.3 parts by mass or more, the charge amount of the toner particles can be stabilized. By making the content of the strontium titanate particles 0.9 parts by mass or less, it is possible to suppress a large amount of the strontium titanate particles from being detached from the toner base particles. As a result, it is possible to suppress the detached strontium titanate particles from hindering the contact between the carrier base particles and the toner particles.
[0070] (Spacer particles) As described above, the external additive preferably further contains spacer particles. The spacer particles suppress contact between the carrier particles and the base silica particles. This allows the spacer particles to suppress the phenomenon in which the surface treatment of the base silica particles peels off due to contact with the carrier particles, and the phenomenon in which the base silica particles are embedded in the toner mother particles due to contact with the carrier particles. The number-average primary particle diameter of the spacer particles is preferably 35 nm or more and 200 nm or less, more preferably 45 nm or more and 140 nm or less, even more preferably 65 nm or more and 120 nm or less, and particularly preferably 90 nm or more and 110 nm or less. By setting the number-average primary particle diameter of the spacer particles to 35 nm or more, the function of the spacer particles can be effectively exhibited. By setting the number-average primary particle diameter of the spacer particles to 200 nm or less, the detachment of the spacer particles from the toner mother particles can be effectively suppressed.
[0071] The number average primary particle diameter of the spacer particles is preferably larger than the number average primary particle diameter of the first strontium titanate particles, which can effectively prevent the first strontium titanate particles from coming into contact with the base silica particles.
[0072] Examples of the spacer particles include silica particles, resin particles, aluminum oxide particles, magnesium oxide particles, zinc oxide particles, and composite particles of these particles. Resin particles are preferred as the spacer particles. By using resin particles as the spacer particles, the melting property of the toner can be optimized.
[0073] The resin contained in the spacer particles is preferably a styrene-(meth)acrylic resin. The content of the styrene-(meth)acrylic resin in the spacer particles is preferably 70% by mass or more, more preferably 95% by mass or more, and even more preferably 100% by mass.
[0074] Styrene-(meth)acrylic resin is a copolymer of a styrene compound and a (meth)acrylic acid compound. Examples of the (meth)acrylic acid compound include (meth)acrylic acid, (meth)acrylonitrile, and (meth)acrylic acid alkyl esters (particularly, (meth)acrylic acid alkyl esters having an alkyl group having 1 to 4 carbon atoms in the ester moiety). As the (meth)acrylic acid compound, (meth)acrylic acid alkyl esters are preferred.
[0075] Examples of the styrene compound include styrene, alkylstyrenes (more specifically, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, ethylstyrene, 2,3-dimethylstyrene, 2,4-dimethylstyrene, o-tert-butylstyrene, m-tert-butylstyrene, and p-tert-butylstyrene), and halogenated styrenes (more specifically, α-chlorostyrene, o-chlorostyrene, m-chlorostyrene, and p-chlorostyrene). As the styrene compound, styrene is preferred.
[0076] The content of the first repeating unit derived from a styrene compound relative to all repeating units contained in the styrene-(meth)acrylic resin is preferably from 5.0% by mass to 50.0% by mass, and more preferably from 15.0% by mass to 25.0% by mass.
[0077] Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, butyl (meth)acrylate (specifically, n-butyl (meth)acrylate), iso-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. As the (meth)acrylic acid alkyl ester, butyl (meth)acrylate is preferred.
[0078] The content ratio of the second repeating unit derived from the (meth)acrylic acid compound relative to all repeating units contained in the styrene-(meth)acrylic resin is preferably 20.0 mass % or more and 60.0 mass % or less, and more preferably 35.0 mass % or more and 45.0 mass % or less.
[0079] From the viewpoint of imparting an appropriate rigidity to the spacer particle, it is preferable that the styrene-(meth)acrylic resin further has a third repeating unit derived from a crosslinking agent. That is, it is preferable that the styrene-(meth)acrylic resin is a crosslinked styrene-(meth)acrylic resin having a first repeating unit derived from a styrene compound, a second repeating unit derived from a (meth)acrylic acid compound, and a third repeating unit derived from a crosslinking agent.
[0080] Examples of the crosslinking agent include compounds having two or more vinyl groups.Specific examples of the crosslinking agent include N,N'-methylenebisacrylamide, divinylbenzene, ethylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, 1,4-butanediol dimethacrylate, and 1,6-hexanediol dimethacrylate.As the crosslinking agent, divinylbenzene is preferable.
[0081] The content ratio of the third repeating unit relative to the total repeating units of the styrene-(meth)acrylic resin is preferably 20.0% by mass or more and 60.0% by mass or less, more preferably 35.0% by mass or more and 45.0% by mass or less. By making the content ratio of the third repeating unit 20.0% by mass or more, the spacer particles are given an appropriate rigidity, and the spacer particles can more easily perform their function as spacers. By making the content ratio of the third repeating unit 60.0% by mass or less, the rigidity of the spacer particles becomes excessively high, and it is possible to suppress abrasion of the surface of the photoreceptor.
[0082] The crosslinked resin preferably has a repeating unit derived from styrene, a repeating unit derived from butyl methacrylate, and a repeating unit derived from divinylbenzene.
[0083] From the viewpoint of fully exerting the function of the spacer particles while suppressing detachment from the toner mother particles, the content of the spacer particles in the toner particles is preferably 0.10 parts by mass or more and 5.00 parts by mass or less, and more preferably 0.20 parts by mass or more and 1.50 parts by mass or less, relative to 100.00 parts by mass of the toner mother particles. By making the content of the spacer particles 0.10 parts by mass or more, it becomes easy to fully exert the function as the spacer particles. By making the content of the spacer particles 5.00 parts by mass or less, it is possible to suppress the spacer particles from being detached from the toner mother particles.
[0084] When the spacer particles are resin particles, the resin particles can be produced by known methods (e.g., suspension polymerization and phase inversion emulsification). Polymerization initiators used in the production of resin particles include, for example, inorganic peroxides (e.g., potassium persulfate, ammonium persulfate, and hydrogen peroxide), organic peroxides (e.g., t-butyl peroxide, cumene hydroxyperoxide, and paramenthane peroxide), and azo compounds (e.g., azobisdiisobutylnitrile and 2,2'-azobis(2-amidinopropane)dihydrochloride), and inorganic peroxides or organic peroxides are preferred.
[0085] (Base silica particles) The base silica particles are preferably silica particles that have been subjected to a surface treatment to impart hydrophobicity. The number-average primary particle diameter of the base silica particles is preferably 10 nm or more and 30 nm or less, more preferably 15 nm or more and 25 nm or less. By making the number-average primary particle diameter of the base silica particles 10 nm or more, it is possible to prevent the base silica particles from being embedded in the toner mother particles. In addition, by making the number-average primary particle diameter of the base silica particles 30 nm or less, it is possible to prevent the base silica particles from being detached from the toner mother particles.
[0086] In order to fully exert the function of the base silica particles while suppressing detachment from the toner base particles, the content of the base silica particles in the toner particles is preferably 0.10 parts by mass or more and 10.00 parts by mass or less, and more preferably 0.50 parts by mass or more and 2.50 parts by mass or less, per 100.00 parts by mass of the toner base particles.
[0087] (Other external additive particles) As the other external additive particles, metal oxide particles (more specifically, aluminum oxide particles, titanium oxide particles, magnesium oxide particles, and zinc oxide particles) are preferred, and aluminum oxide particles are more preferred. The number average primary particle size of the aluminum oxide particles is preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 20 nm or less.
[0088] The content of the other external additives is preferably from 0.10 parts by mass to 5.00 parts by mass, and more preferably from 0.50 parts by mass to 1.00 parts by mass, relative to 100.00 parts by mass of the toner base particles, from the viewpoint of suppressing detachment from the toner base particles while fully exerting its function.
[0089] (Toner base particles) The toner base particles contain, for example, a binder resin and at least one selected from the group consisting of a colorant, a charge control agent, and a release agent. In the toner base particles, the content of the binder resin is preferably 70% by mass or less and 97% by mass or less, and more preferably 80% by mass or more and 93% by mass or less. The binder resin, the colorant, the charge control agent, and the release agent will be described below.
[0090] (Binding resin) In order to obtain a toner having excellent low-temperature fixing properties, the toner base particles preferably contain a thermoplastic resin as a binder resin, and more preferably contain a thermoplastic resin at a ratio of 85% by mass or more of the total binder resin. Examples of the thermoplastic resin include polyester resin, styrene resin, acrylic acid ester resin (more specifically, acrylic acid ester polymer, methacrylic acid ester polymer, etc.), olefin resin (more specifically, polyethylene resin, polypropylene resin, etc.), vinyl resin (more specifically, vinyl chloride resin, polyvinyl alcohol, vinyl ether resin, N-vinyl resin, etc.), polyamide resin, and urethane resin. In addition, copolymers of these resins, that is, copolymers in which any repeating unit is introduced into the above resin (more specifically, styrene-acrylic resin, styrene-butadiene resin, etc.) can also be used as the binder resin.
[0091] The binder resin is preferably a polyester resin. The polyester resin is a polymer of one or more polyhydric alcohol monomers and one or more polycarboxylic acid monomers. Instead of the polycarboxylic acid monomer, a polycarboxylic acid derivative (more specifically, a polycarboxylic acid anhydride, a polycarboxylic acid halide, etc.) may be used.
[0092] Examples of polyhydric alcohol monomers include diol monomers, bisphenol monomers, and trihydric or higher alcohol monomers.
[0093] Diol monomers include, for example, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 2-butene-1,4-diol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,4-benzenediol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0094] Examples of bisphenol monomers include bisphenol A, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts of bisphenol A.
[0095] Examples of trihydric or higher alcohol monomers include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, diglycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0096] Examples of polycarboxylic acid monomers include dicarboxylic acid monomers and tri- or higher carboxylic acid monomers.
[0097] Examples of divalent carboxylic acid monomers include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalate, cyclohexanedicarboxylic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, succinic acid, alkyl succinic acid, and alkenyl succinic acid. Examples of alkyl succinic acid include n-butyl succinic acid, isobutyl succinic acid, n-octyl succinic acid, n-dodecyl succinic acid, and isododecyl succinic acid. Examples of alkenyl succinic acid include n-butenyl succinic acid, isobutenyl succinic acid, n-octenyl succinic acid, n-dodecenyl succinic acid, and isododecenyl succinic acid.
[0098] Examples of trivalent or higher carboxylic acid monomers include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, and empol trimer acid.
[0099] The polyester resin is preferably a polymer of a bisphenol monomer, a divalent carboxylic acid monomer, and a trivalent carboxylic acid monomer, and more preferably a polymer of a bisphenol A alkylene oxide adduct, terephthalic acid, isophthalic acid, and trimellitic acid.
[0100] The polyester resin is preferably an amorphous polyester resin. For amorphous polyester resins, it is often impossible to measure a clear melting point. Therefore, a polyester resin that does not show a clear endothermic peak in an endothermic curve measured using a differential scanning calorimeter may be judged to be an amorphous polyester resin.
[0101] The softening point (Tm) of the polyester resin is preferably 70° C. or more and 130° C. or less, and more preferably 90° C. or more and 110° C. or less. By setting the softening point of the polyester resin to 70° C. or more, it is possible to impart excellent hot offset resistance to the toner. By setting the softening point of the polyester resin to 130° C. or less, it is possible to impart excellent low-temperature fixing property to the toner.
[0102] The glass transition point (Tg) of the polyester resin is preferably 30° C. or higher and 80° C. or lower, and more preferably 40° C. or higher and 60° C. or lower. By setting the glass transition point of the polyester resin to 30° C. or higher, it is possible to impart excellent heat-resistant storage stability to the toner. By setting the glass transition point of the polyester resin to 100° C. or lower, it is possible to impart excellent low-temperature fixing property to the toner.
[0103] (Coloring agent) As the colorant, a known pigment or dye can be used in accordance with the color of the toner, and examples of the colorant include a black colorant, a yellow colorant, a magenta colorant, and a cyan colorant.
[0104] An example of the black colorant is carbon black. The black colorant may be a colorant that is toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0105] In the toner base particles, the content of the colorant is preferably from 1 to 20 parts by mass, and more preferably from 3 to 7 parts by mass, relative to 100 parts by mass of the binder resin.
[0106] (Charge control agent) The charge control agent is used, for example, for the purpose of obtaining a toner having excellent charge stability and charge rise characteristics. The charge rise characteristics of the toner are an index of whether the toner can be charged to a predetermined charge level in a short time. Examples of the charge control agent include a positive charge control agent and a negative charge control agent. The cationic property (positive chargeability) of the toner can be strengthened by adding a positive charge control agent to the toner base particles, and the anionic property (negative chargeability) of the toner can be strengthened by adding a negative charge control agent to the toner base particles. Examples of the positive charge control agent include pyridine, nigrosine, and quaternary ammonium salts. Examples of the negative charge control agent include metal-containing azo dyes, sulfo group-containing resins, oil-soluble dyes, naphthenic acid metal salts, acetylacetone metal complexes, salicylic acid metal complexes, boron compounds, fatty acid soaps, and long-chain alkyl carboxylates. However, if sufficient chargeability is ensured in the toner, it is not necessary to add a charge control agent to the toner base particles. In the toner base particles, the content of the charge control agent is preferably from 0.1 to 5 parts by mass, and more preferably from 0.5 to 2 parts by mass, relative to 100 parts by mass of the binder resin.
[0107] (Release agent) The release agent is used, for example, for the purpose of obtaining a toner having excellent hot offset resistance. Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, plant-derived waxes, animal-derived waxes, mineral-derived waxes, ester waxes mainly composed of fatty acid esters, and waxes in which fatty acid esters are partially or completely deoxidized. Examples of the aliphatic hydrocarbon waxes include polyethylene waxes (e.g., low molecular weight polyethylene), polypropylene waxes (e.g., low molecular weight polypropylene), polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the plant-derived waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal-derived waxes include beeswax, lanolin, and spermaceti. Examples of the mineral-derived waxes include ozokerite, ceresin, and petrolatum. Examples of ester waxes mainly composed of fatty acid ester include Montan acid ester wax and castor wax. Examples of waxes in which fatty acid ester is partially or completely deoxidized include deoxidized carnauba wax. In the toner base particles, the content of the release agent is preferably 1 part by mass or more and 20 parts by mass or less, more preferably 3 parts by mass or more and 10 parts by mass or less, based on 100 parts by mass of the binder resin.
[0108] The toner particles may further contain known additives as necessary. The volume median diameter of the toner particles is preferably 4.0 μm or more and 12.0 μm or less. The volume median diameter of the toner base particles is preferably 4.0 μm or more and 12.0 μm or less, and more preferably 5.0 μm or more and 9.0 μm or less. The toner particles are preferably non-magnetic toner.
[0109] (Toner manufacturing method) An example of a toner manufacturing method will be described. The toner manufacturing method includes a toner base particle preparation step of preparing toner base particles, and an external additive step of attaching an external additive to the surface of the toner base particles. The external additive includes at least strontium titanate particles.
[0110] (Toner base particle preparation process) In the toner base particle preparation step, the toner base particles are prepared by, for example, a pulverization method or an aggregation method. In the toner base particle preparation step, the toner base particles are preferably prepared by a pulverization method. That is, in the toner, the toner base particles are preferably pulverized toner base particles.
[0111] In one example of the pulverization method, first, a binder resin is mixed with other components added as necessary. The resulting mixture is then melt-kneaded using a melt-kneading device (e.g., a single-screw or twin-screw extruder). The resulting melt-kneaded product is then pulverized and classified. This produces toner base particles.
[0112] In one example of the aggregation method, first, in an aqueous medium containing fine particles of a binder resin and other components added as necessary, these fine particles are aggregated until they reach a desired particle size. This forms aggregated particles containing the binder resin and the like. The resulting aggregated particles are then heated to unify the components contained in the aggregated particles. This gives toner base particles.
[0113] (External addition process) In this process, the external additive is attached to the surface of the toner base particle. For example, a method of attaching the external additive to the surface of the toner base particle may be used to mix the toner base particle and the external additive while stirring them using a mixing device. When the external addition process is performed using an FM mixer, the mixing time is preferably 2.0 minutes or more and 15.0 minutes or less, and more preferably 3.0 minutes or more and 7.0 minutes or less. The stirring speed is preferably 1000 rpm or more and 5000 rpm or less, and more preferably 2500 rpm or more and 3500 rpm or less.
[0114] Second embodiment: Image forming apparatus The second embodiment of the present invention relates to an image forming apparatus. The image forming apparatus of this embodiment includes the developer of the first embodiment, a photoconductor, a charging device that charges the surface of the photoconductor, and a developing device that supplies toner to the surface of the photoconductor and develops it into a toner image. The above-mentioned printing durability test is performed using the image forming apparatus. The image forming apparatus of this embodiment uses the developer of the first embodiment, so that the occurrence of fogging can be suppressed.
[0115] An image forming apparatus 40, which is an example of the image forming apparatus of this embodiment, will be described below with reference to Fig. 2. The image forming apparatus 40 shown in Fig. 2 includes developers (developer D in use and replenishment developer E, see Fig. 3), photoconductors 41a to 41d, charging devices 42a to 42d, an exposure device 43, developing devices 44a to 44d, a transfer device 45, a fixing device 46, a cleaning device 47, and a control unit 48. Hereinafter, unless there is a need to distinguish between them, each of the photoconductors 41a to 41d will be referred to as a photoconductor 41, each of the charging devices 42a to 42d will be referred to as a charging device 42, and each of the developing devices 44a to 44d will be referred to as a developing device 44.
[0116] The developer D in use includes an initial developer and a replenishment developer E. At least one of the initial developer and the replenishment developer E is the developer of the first embodiment, and it is preferable that the initial developer is the developer of the first embodiment, and it is more preferable that both the initial developer and the replenishment developer E are the developers of the first embodiment.
[0117] The photoreceptor 41 is cylindrical. The photoreceptor 41 has a metal cylinder (e.g., a cylindrical conductive substrate) as a core material. A photosensitive layer is provided on the outside of the core material. The photoreceptor 41 is supported so as to be rotatable. The photoreceptor 41 is driven to rotate by, for example, a motor (not shown).
[0118] The charging device 42 charges the peripheral surface of the photoconductor 41 .
[0119] The exposure device 43 exposes the charged peripheral surface of the photoreceptor 41 to light, thereby forming an electrostatic latent image on the peripheral surface of the photoreceptor 41. For example, an electrostatic latent image is formed on the surface layer portion (photosensitive layer) of the photoreceptor 41 based on image data.
[0120] The developing device 44 develops the electrostatic latent image with the in-use developer D. More specifically, the developing device 44 develops the electrostatic latent image formed on the peripheral surface of the photoconductor 41 with the in-use developer D, and develops the electrostatic latent image into a toner image. Details of the developing device 44 will be described later.
[0121] The transfer device 45 includes a transfer belt 51, a drive roller 52, a driven roller 53, a tension roller 54, primary transfer rollers 55a to 55d, and a secondary transfer roller 56. Hereinafter, when there is no need to distinguish between them, each of the primary transfer rollers 55a to 55d will be referred to as a primary transfer roller 55. The transfer belt 51 is an endless belt stretched around the drive roller 52, the driven roller 53, and the tension roller 54. As the drive roller 52 rotates, the transfer belt 51 is transported in the clockwise direction in FIG. 2 (the direction of the arrow d1 in FIG. 2). As the transfer belt 51 is transported, the driven roller 53 and the tension roller 54 are driven to rotate.
[0122] After the toner images are formed on the photoconductors 41a to 41d, a bias (voltage) is applied to the primary transfer rollers 55a to 55d, whereby the toner attached to the photoconductors 41a to 41d is sequentially primarily transferred onto the transfer belt 51. In this manner, toner images of multiple colors are superimposed on the transfer belt 51. After the primary transfer, a bias (voltage) is applied to the secondary transfer roller 56, whereby the toner images of multiple colors on the transfer belt 51 are secondarily transferred onto the recording medium P (for example, printing paper) being conveyed. Then, the toner images of multiple colors superimposed on the transfer belt 51 are secondarily transferred collectively onto the recording medium P. In this manner, an image composed of unfixed toner is formed on the recording medium P.
[0123] After the secondary transfer, the fixing device 46 heats and pressurizes the toner on the recording medium P to fix the toner to the recording medium P. In this manner, an image made of the fixed toner is formed on the recording medium P.
[0124] The cleaning device 47 cleans the toner remaining on the transfer belt 51 after the secondary transfer.
[0125] The control unit 48 electronically controls the operation of the image forming apparatus 40 based on the outputs of various sensors. The control unit 48 includes, for example, a central processing unit (CPU), a random access memory (RAM), and a storage device that stores programs and rewritably stores predetermined data. A user gives instructions (for example, electrical signals) to the control unit 48 through an input unit (not shown). The input unit is, for example, a keyboard, a mouse, or a touch panel.
[0126] Next, the developing device 44 will be described in more detail with reference to FIG. 3. FIG. 3 shows the developing device 44 and its surroundings of the image forming apparatus 40 shown in FIG. 2. The developing device 44 has at least a container 114. The developing device 44 further has a developer carrier 111, a regulating blade 112, a plurality of stirring shafts 113, a supply section 115, and a discharge section 116. The developing device 44 has the container 114, the supply section 115, and the discharge section 116, and is a so-called trickle development type developing device 44.
[0127] The storage section 114 stores the in-use developer D and a plurality of stirring shafts 113. The in-use developer D stored in the storage section 114 includes an initial developer. The plurality of stirring shafts 113 include a first stirring shaft 113a and a second stirring shaft 113b. The first stirring shaft 113a has a spiral stirring blade. The second stirring shaft 113b has a spiral stirring blade that faces in the opposite direction (opposite phase) to the spiral blade of the first stirring shaft 113a. The first stirring shaft 113a stirs the in-use developer D in the storage section 114, and transports the in-use developer D in a first transport direction (a direction perpendicular to the paper surface of FIG. 3 and a direction from the back to the front of the paper surface) from one end side to the other end side in the axial direction of the developer carrier 111. The second agitating shaft 113b transports the in-use developer D in a second transport direction opposite to the first transport direction while agitating the in-use developer D in the storage section 114. As the in-use developer D, which contains toner and carrier, is agitated, the toner is charged by friction with the carrier, and the charged toner is carried by the carrier. The second agitating shaft 113b supplies the in-use developer D to the developer carrier 111 while transporting the in-use developer D in the second transport direction.
[0128] The replenishing section 115 is provided above the containing section 114. The replenishing section 115 replenishing the replenishing developer E to the containing section 114. The replenishing section 115 has a replenishing amount adjusting member 115a and a developer container 115b.
[0129] The supply amount adjustment member 115a controls the supply amount of the replenishment developer E supplied from the developer container 115b to the storage portion 114. The supply amount adjustment member 115a is composed of, for example, a screw shaft whose rotation operation is controlled by the control portion 48. For example, the supply amount of the replenishment developer E can be changed according to the amount of rotation of the screw shaft.
[0130] The developer container 115b accommodates the replenishment developer E. The replenishment developer E in the developer container 115b is supplied to the accommodation portion 114.
[0131] The discharge section 116 discharges the developer D in use from the storage section 114. The discharge section 116 includes a discharge path 116a and a collection container 116b. The discharge path 116a connects the storage section 114 and the collection container 116b. When the amount of the developer D in use in the storage section 114 exceeds a predetermined amount, the excess developer D in use enters the discharge path 116a from the opening on the upper end side of the discharge path 116a. The predetermined amount is, for example, an amount determined by the upper end position of the discharge path 116a. The excess developer D in use is, for example, the amount of developer D in use that exceeds the predetermined amount. When the excess developer D in use enters the discharge path 116a, it advances downward inside the discharge path 116a by gravity and flows into the collection container 116b. Then, the collection container 116b stores the excess developer D in use. Hereinafter, the collected developer is referred to as a collected developer F.
[0132] In the image forming apparatus 40 before starting image formation (for example, an unused image forming apparatus 40), the developer D in use accommodated in the accommodation portion 114 is an initial developer.
[0133] After image formation is started, before the replenishing unit 115 replenishes the replenishment developer E into the storage unit 114, the developer D in use contained in the storage unit 114 is the initial developer. In the storage unit 114, the initial developer is stirred by the stirring shaft 113, and the toner particles 4 contained in the initial developer are triboelectrically charged. Then, the stirred initial developer is carried on the developer carrier 111.
[0134] As printing by the image forming device 40 continues, the replenishment developer E is replenished into the storage unit 114, and the used developer D is discharged from the storage unit 114. Therefore, as printing by the image forming device 40 continues, the used developer D stored in the storage unit 114 is gradually replaced with the replenishment developer E replenished from the replenishing unit 115. After the replenishing unit 115 replenishes the replenishment developer E into the storage unit 114, the initial developer and the replenishment developer E are stirred by the stirring shaft 113 in the storage unit 114, and the toner particles 4 contained in the initial developer and the toner particles 4 contained in the replenishment developer E are triboelectrically charged. Then, the stirred initial developer and the replenishment developer E are carried on the developer carrying member 111.
[0135] The developer carrier 111 is disposed near the photoconductor 41. The developer carrier 111 includes a magnet roll and a developing sleeve. The magnet roll has magnetic poles at least on its surface. The magnetic poles are, for example, N and S poles based on permanent magnets. The developing sleeve is a non-magnetic cylinder (for example, an aluminum pipe). The magnet roll is located inside the developing sleeve (inside the cylinder), and the developing sleeve is located on the surface of the developer carrier 111. The shaft of the magnet roll and the developing sleeve are connected via a flange so that the developing sleeve can rotate around the non-rotating magnet roll.
[0136] As already described, the charged toner is carried by the carrier in the storage section 114. The developer carrier 111 (specifically, the developing sleeve) attracts the carrier in the storage section 114 by magnetic force while rotating in the clockwise direction in FIG. 3 (the direction of the arrow d2 in FIG. 3), and carries the carrier carrying the toner (i.e., the developer in use D) on its circumferential surface. Then, a magnetic brush is formed by the developer in use D carried by the developer carrier 111.
[0137] The regulating blade 112 regulates the thickness of the magnetic brush of the developer D in use formed on the circumferential surface of the developer carrier 111 to a predetermined thickness.
[0138] After the thickness of the magnetic brush is regulated by the regulating blade 112, the developer carrier 111 (specifically, the developing sleeve) further rotates in the clockwise direction (the direction of the arrow d2 in FIG. 3), and the in-use developer D is transported to the closest portion N between the photoconductor 41 and the developer carrier 111. The photoconductor 41 rotates in the counterclockwise direction in FIG. 3 (the direction of the arrow d3 in FIG. 3). A bias (voltage) is applied to the developer carrier 111, causing a potential difference to occur between the surface potential of the developer carrier 111 and the surface potential of the photoconductor 41. This potential difference causes the toner contained in the in-use developer D carried by the developer carrier 111 to move to the circumferential surface of the photoconductor 41. Specifically, the charged toner contained in the in-use developer D carried on the developer carrier 111 is attracted by an electric force to an electrostatic latent image (for example, an exposed portion where the potential has been lowered by exposure to light compared to a non-exposed portion) formed on the photoreceptor 41, and moves to the electrostatic latent image on the photoreceptor 41. As a result, a toner image is formed on the surface of the photoreceptor 41.
[0139] The image forming apparatus 40 has been described above with reference to Figs. 2 and 3. However, the image forming apparatus of this embodiment is not limited to the image forming apparatus 40 of Figs. 2 and 3, and can be modified in various ways without departing from the gist of the present invention. For example, some components may be deleted from all the components. Furthermore, the material, shape, dimensions, etc. of each component are merely examples and are not particularly limited, and various modifications are possible. EXAMPLES
[0140] The present invention will be described in more detail below using examples, but the present invention is not limited to the scope of the examples.
[0141] [Measurement of saturation magnetization and coercivity] In this example, the saturation magnetization and coercivity of the carrier core were measured using a high-sensitivity vibrating sample magnetometer ("VSM-P7" manufactured by Toei Kogyo Co., Ltd.) under the condition of an applied magnetic field of 3000 Oe.
[0142] Volume median diameter of powder (D 50The measured values of (a) and (b) were measured using a laser diffraction / scattering type particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.).
[0143] [Measurement of number average primary particle size] The number-average primary particle diameter of the particles was measured using a scanning electron microscope (field emission scanning electron microscope, "JSM-7600F" manufactured by JEOL Ltd.) In measuring the number-average primary particle diameter, the circle-equivalent diameters (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) of 100 primary particles were measured, and the number-average value was calculated.
[0144] (Synthesis of amorphous polyester resin) A 5L reaction vessel equipped with a thermometer (thermocouple), a dehydration tube, a nitrogen introduction tube, and a stirring device (stirring blade) was set in an oil bath. 1575g of BPA-PO (bisphenol A propylene oxide adduct), 163g of BPA-EO (bisphenol A ethylene oxide adduct), 377g of fumaric acid, and 4g of catalyst (dibutyltin oxide) were charged into the reaction vessel. After that, a nitrogen atmosphere was created in the reaction vessel, and the temperature in the reaction vessel was raised to 220°C using an oil bath while stirring the contents.
[0145] The contents of the reaction vessel were polymerized for 8 hours under conditions of nitrogen atmosphere and temperature 220°C while distilling off by-product water. Then, after reducing the pressure in the reaction vessel, the contents of the reaction solution were polymerized for another hour under conditions of reduced pressure atmosphere (pressure: 8 kPa) and temperature 220°C. Then, the temperature in the reaction vessel was lowered to 210°C, and 336 g of trimellitic anhydride was added to the reaction vessel. Then, the contents of the reaction vessel were reacted under conditions of reduced pressure atmosphere (pressure: 8 kPa) and temperature 210°C. The reaction time in the reaction was adjusted so that the softening point (Tm) of the reaction product (amorphous polyester resin) was 100°C and the glass transition point (Tg) was 50°C. Then, the reaction product was taken out of the reaction vessel and cooled to obtain an amorphous polyester resin.
[0146] (Preparation of toner base particles) Using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts by mass of binder resin, 4 parts by mass of colorant, 1 part by mass of charge control agent, and 5 parts by mass of release agent were mixed. As the binder resin, 100 parts by mass of the above-mentioned amorphous polyester resin (Tm: 100°C, Tg: 50°C) was used. As the colorant, copper phthalocyanine blue pigment (CI Pigment Blue 15:3) was used. As the charge control agent, quaternary ammonium salt ("BONTRON (registered trademark) P-51" manufactured by Orient Chemical Industries Co., Ltd.) was used. As the release agent, carnauba wax ("Special Carnauba Wax No. 1" manufactured by Kato Yoko Co., Ltd.) was used.
[0147] The resulting mixture was melt-kneaded using a twin-screw extruder (Ikegai Corporation, "PCM-30 type"). The resulting melt-kneaded product was pulverized using a mechanical pulverizer (Freund Turbo Corporation, "Turbo Mill"). The pulverized product was classified using a classifier (Nitetsu Mining Co., Ltd., "Elbow Jet"). This resulted in a volume median diameter (D 50 Powdered toner base particles having a particle diameter of 6.8 μm were obtained.
[0148] [Preparation of resin particles] A glass reaction vessel equipped with a thermometer (thermocouple), a stirrer, a reflux condenser, and a nitrogen inlet tube was set in a water bath (set temperature: 80°C). 300.0 parts by mass of ion-exchanged water and 1.0 parts by mass of di-t-butyl peroxide were added to this reaction vessel. Next, the inside of the reaction vessel was placed under a nitrogen gas atmosphere. In the subsequent operations, the temperature of the contents of the reaction vessel was kept at 80°C, and the inside of the reaction vessel was kept under a nitrogen gas atmosphere. Next, while stirring the reaction vessel, 0.2 parts by mass of ammonium persulfate and 60.0 parts by mass of the monomer mixture were dropped into the reaction vessel over 1 hour. The monomer mixture was a mixture of 10 mol% styrene, 40 mol% butyl methacrylate, and 50 mol% divinylbenzene. Next, the contents were reacted while stirring the reaction solution. In this reaction, the reaction temperature (hereinafter sometimes referred to as "temperature T") was 100°C, the reaction time (hereinafter sometimes referred to as "time Y") was 4 hours, and the stirring speed (hereinafter sometimes referred to as "speed Z") was 756 rpm. The reaction solution (emulsion solution) after the reaction was dried to obtain resin particles (number average primary particle diameter: 100 nm) containing a crosslinked resin.
[0149] [Toner Preparation] (Toner (T-1)) 100.00 parts by mass of the above-mentioned toner base particles, 1.50 parts by mass of base silica particles, 0.50 parts by mass of spacer particles, 0.75 parts by mass of aluminum oxide particles, and 0.50 parts by mass of strontium titanate particles were mixed for 5.0 minutes at 3,000 rpm using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.) (hereinafter, this mixing time will be referred to as external addition time T1). The resulting mixture was sieved using a sieve with a mesh size of 200 (opening size of 75 μm) to obtain a toner (T-1). As the base silica particles, "AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd. (fumed silica with positive charging and hydrophobicity imparted by surface treatment, number average primary particle diameter: 20 nm) was used. As the spacer particles, the above-mentioned resin particles (number average primary particle diameter: 100 nm) were used. The aluminum oxide particles were "AEROXIDE (registered trademark) Alu C805" (BET specific surface area: 75 to 105 m) manufactured by Nippon Aerosil Co., Ltd. 2 / g, number average primary particle diameter 13 nm) was used. As the strontium titanate particles, undoped strontium titanate particles with a particle size adjusted to a number average primary particle diameter of 30 nm (particle size adjusted product "SW-100" manufactured by Titan Kogyo Co., Ltd.) were used.
[0150] (Toner (T-2)~(T-12)) Toners (T-2) to (T-12) were prepared in the same manner as toner (T-1), except that the type, amount, and external addition time T1 of the strontium titanate particles used were changed as shown in Table 1 below.
[0151] [Table 1]
[0152] [Preparation of carrier] Carriers (C-1) to (C-18) were prepared by the following method.
[0153] (Preparation of Carrier (C-1)) A coating liquid was obtained by mixing 361.2 g of a silicone resin solution ("KR-255" manufactured by Shin-Etsu Chemical Co., Ltd., solid concentration: 50 mass%, solid content: 180.6 g), 36.2 g of barium titanate particles ("BT-03" manufactured by Sakai Chemical Industry Co., Ltd., barium titanate particles produced by a hydrothermal synthesis method, number average primary particle diameter: 300 nm), 14.4 g of carbon black ("Ketjen Black EC-300J" manufactured by Lion Specialty Chemicals Co., Ltd.) and 1444.8 g of toluene using a homomixer.
[0154] Using a fluidized bed coating device (Powrex Corporation, "FD-MP-01 D type"), 5000 g of carrier cores were fluidized while spraying the coating liquid onto the carrier cores. In this way, carrier cores coated with the coating liquid were obtained. The amount of coating liquid used was an amount such that the mass of the coating layer was 1.5 parts by mass (i.e., an amount such that the solid content was 75 g) per 100.0 parts by mass of carrier cores. The coating conditions were an inlet air temperature (corresponding to the predetermined drying temperature described in the embodiment) of 75°C, an inlet air volume of 0.3 m3, and a carrier core diameter of 1.5 mm. 3 The conditions were: 1.5 rpm / min, and the rotor rotation speed was 400 rpm. Manganese ferrite cores (manufactured by DOWA IP Creation Co., Ltd., volume median diameter: 20.3 μm, saturation magnetization: 67 emu / g) were used as carrier cores. The carrier cores coated with the coating liquid were fired at a temperature of 200° C. for 1 hour using an electric furnace. In this way, a coating layer was formed on the surface of the carrier cores, and carrier base particles were obtained.
[0155] 100.00 parts by mass of the above-mentioned carrier base particles and 0.04 parts by mass of strontium titanate particles were mixed for 15.0 minutes using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10") to attach the strontium titanate particles to the surface of the carrier base particles (hereinafter, the mixing time in the preparation of the carrier is referred to as the external addition time T2). As the strontium titanate particles, non-doped strontium titanate particles (particle size adjusted product of "SW-100" manufactured by Titan Kogyo Co., Ltd.) with a number average primary particle diameter of 30 nm were used. Thus, carrier (C-1) was obtained.
[0156] (Preparation of Carriers (C-2) to (C-18)) Carriers (C-2) to (C-18) were prepared in the same manner as in the preparation of carrier (C-1), except that the amount and number average primary particle diameter of barium titanate particles used in forming the coating layer, the amount and number average primary particle diameter of strontium titanate first particles used, and the external addition time T2 were changed as shown in Table 3 below. In Table 2 below, "particle diameter" indicates the number average primary particle diameter. The parts by mass of the strontium titanate first particles indicate the parts by mass relative to 100.00 parts by mass of the carrier mother particles. The parts by mass of the barium titanate particles indicate the parts by mass relative to 100 parts by mass of the coating resin.
[0157] The strontium titanate particles used in the preparation of carriers (C-2) to (C-18) were all undoped strontium titanate particles (particle size adjusted product of "SW-100" manufactured by Titan Kogyo Co., Ltd.).
[0158] [Table 2]
[0159] <Preparation of Developer> (Developer (D-1)) Using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10"), 8 parts by mass of toner (T-1) and 92 parts by mass of carrier (C-1) were mixed for 30 minutes to obtain developer (D-1) (toner concentration: 8% by mass), which is an initial developer.
[0160] Using a rocking mixer (registered trademark) (Aichi Electric Co., Ltd. "RM-10"), 90 parts by mass of the above toner and 10 parts by mass of the above carrier were mixed for 30 minutes. This resulted in a refill developer corresponding to developer (D-1).
[0161] (Developer (D-2)~(D-27)) Except for changing the combination of toner and carrier as shown in Table 3 below, developers (D-2) to (D-27) were prepared in the same manner as developer (D-1). In addition, replenishment developers corresponding to developers (D-2) to (D-27) were obtained in the same manner as the preparation of the replenishment developer corresponding to developer (D-1). In Table 3, "diameter" indicates the number average primary particle diameter. The parts by mass of the second strontium titanate particles in the toner indicate the parts by mass relative to 100.0 parts by mass of the toner mother particles. The parts by mass of the first strontium titanate particles in the carrier indicate the parts by mass relative to 100.00 parts by mass of the carrier mother particles. The parts by mass of the barium titanate particles indicate the parts by mass relative to 100 parts by mass of the coating resin.
[0162] [Table 3]
[0163] [Evaluation machine] A trickle development type color multifunction printer (TASKalfa7054ci manufactured by Kyocera Document Solutions Inc.) was prepared as the evaluation machine. This color multifunction printer was mainly equipped with an amorphous silicon drum as a photoconductor and a two-component development device. The maximum printing speed of the above color multifunction printer was 70 sheets per minute. The development gap of the above color multifunction printer was 0.375 mm. When printing A4 size printing paper, the above color multifunction printer printed so that the width direction of the printing paper and the printing direction were aligned.
[0164] [Measurement of desorption rate] Any one of the developers (D-1) to (D-27) was loaded into the cyan developing device of the evaluation machine. Furthermore, a refill developer corresponding to each developer was loaded into the refill section of the cyan developing device of the evaluation machine. By carrying out a printing test using the evaluation machine, the detachment rate N of the first strontium titanate particles from the carrier particles (specifically, the detachment rate N of the first strontium titanate particles from the carrier particles) was measured. 100 Or at time t 1000 The detachment rate N at time t1, the detachment rate L of the strontium titanate particles in the toner particles (more specifically, 100 Or at time t 1000 The desorption rate L at time t1 and time t2 were measured. The measurement results are shown in Table 4 below. 100 Or at time t 1000 The ratio (N / L) at
[0165] In detail, in an environment of a temperature of 23°C and a humidity of 5% RH, an evaluation machine was used to print a pattern image (character pattern image) with a print rate of 1% on a sheet of A4-sized printing paper using each developer and a replenishment developer (printing test A).
[0166] Immediately after the printing test A, a magnet was brought close to the developing roller to which the developer was attached, and the developer was peeled off from the developing roller and collected. The collected developer was sucked with air through a mesh. As a result, the toner (toner at time t1) and carrier (carrier at time t1) were collected.
[0167] A new evaluation machine was prepared separately, and printing test B was carried out under the same conditions as printing test A, except that the number of printed sheets was changed to 100 and intermittent printing was performed. In printing test B, a cycle of printing for 4.3 seconds and pausing printing for about 0.5 seconds was repeated. Then, for the evaluation machine immediately after printing test B, a magnet was brought close to the developing roller to which the developer was attached, to peel off and collect the developer from the developing roller. The collected developer was sucked with air through a mesh. As a result, the toner (at time t 100 toner at time t 100 The carriers) and
[0168] A new evaluation machine was prepared separately, and printing test C was carried out under the same conditions as printing test B, except that the number of printed sheets was changed to 1000 sheets. Then, for the evaluation machine immediately after printing test C, a magnet was brought close to the developing roller to which the developer was attached, and the developer was peeled off from the developing roller and collected. The collected developer was sucked with air through a mesh. As a result, the toner (at time t 1000 toner at time t 1000 The carriers) and
[0169] The above-mentioned time t1 and time t 100 Or at time t 1000 The carrier was subjected to X-ray fluorescence analysis by the following method. 100 Or at time t 1000 The content Q1 (Sr intensity) of the first strontium titanate particles in the carrier particles was measured. 100 Or at time t 1000 The toner was subjected to fluorescent X-ray analysis by the following method. 100 Or at time t 1000 The content Q2 of strontium titanate particles (Sr intensity) in the toner particles was measured.
[0170] The developer before the printing test, which was prepared separately, was sucked with air through a mesh. As a result, the toner (toner before the printing test) and the carrier (carrier before the printing test) were collected. Each toner and carrier was subjected to fluorescent X-ray analysis by the following method. As a result, the content P2 (Sr intensity) of strontium titanate particles in the toner particles before the printing test and the content P1 (Sr intensity) of strontium titanate particles in the carrier particles before the printing test were measured.
[0171] The above-mentioned time t1 and time t 100 Or at time t 1000 The content Q1 of the first strontium titanate particles in the carrier particles at time t1 and the content P1 of the first strontium titanate particles in the carrier particles before the printing test were applied to the following formula. 100 , or time t 1000 The detachment rate N of the strontium titanate particles was calculated. The results are shown in Table 4. N = 100 × (P1-Q1) / P1
[0172] The above-mentioned time t1 and time t 100 Or at time t 1000 The content Q2 of the strontium titanate particles in the toner particles at time t1 and the content P2 of the strontium titanate particles in the toner particles before the printing test were applied to the following formula. 100 , or time t 1000 The detachment rate L of the strontium titanate particles was calculated. The results are shown in Table 4. L = 100 × (P2-Q2) / P2
[0173] (X-ray fluorescence analysis of toner) The content of strontium titanate particles in the toner particles was measured by the following method. Using a tablet press ("BRE-33" manufactured by Mayekawa Test Machinery Manufacturing Co., Ltd.), the measurement object (toner) was pressurized (pressure: 20 MPa, pressurization time: 3 seconds) to prepare a cylindrical pellet with a diameter of 10 mm. The obtained pellet was subjected to fluorescent X-ray analysis under the detailed conditions shown below to obtain a fluorescent X-ray spectrum (horizontal axis: energy, vertical axis: intensity (number of photons)). From the obtained fluorescent X-ray spectrum, the X-ray intensity (Sr intensity) of the peak derived from the measured element (strontium) was obtained. The above-mentioned Sr intensity was taken as a measured value corresponding to the content of strontium titanate particles.
[0174] (X-ray fluorescence analysis of carrier) The content of the strontium titanate particles in the carrier particles was measured by the following method. A conductive tape (diameter 30 mm) was fixed with the adhesive surface facing outward. The measurement target (carrier particles) was scattered on the adhesive surface of the conductive tape. Next, excess measurement target was removed from the adhesive surface by air blowing. Next, a medicine wrapping paper was placed on the adhesive surface, and a load was applied to the measurement target via the medicine wrapping paper, thereby fixing the measurement target to the conductive tape. Next, the medicine wrapping paper was peeled off from the adhesive surface of the conductive tape. As a result, a sample including the conductive tape and the measurement target dispersed and fixed on the adhesive surface of the conductive tape was obtained. The obtained sample was subjected to fluorescent X-ray analysis under the detailed conditions shown below, and a fluorescent X-ray spectrum (horizontal axis: energy, vertical axis: intensity (number of photons)) was obtained. From the obtained fluorescent X-ray spectrum, the X-ray intensity (Sr intensity) of the peak derived from the measurement element (strontium) was obtained. The above-mentioned Sr intensity was taken as a measured value corresponding to the content of the strontium titanate particles.
[0175] (Details of X-ray fluorescence analysis conditions) Analytical equipment: Scanning X-ray fluorescence analyzer (Rigaku Corporation "ZSX PrimusIV") X-ray tube (X-ray source): Rh (rhodium) Excitation conditions: Tube voltage 50 kV, tube current 50 mA Measurement area (X-ray irradiation range): diameter 30 mm Measurement element: Strontium
[0176] [Table 4]
[0177] <Evaluation> The developers (D-1) to (D-27) were evaluated for the occurrence of fogging by the following method. The evaluation results are shown in Table 5.
[0178] One of the developers (D-1) to (D-27) was put into the cyan developing device of the evaluation machine. Furthermore, a refill developer corresponding to each developer was put into the refill section of the cyan developing device of the evaluation machine. In an environment of 23°C temperature and 5% RH, a pattern image (character pattern image) with a print rate of 1% was printed on one sheet of A4 size printing paper using the evaluation machine with each developer and refill developer put in. Then, a first evaluation image consisting of only a blank image was printed on the printing paper.
[0179] Next, using the evaluation machine, a pattern image (character pattern image) with a print rate of 1% was intermittently printed on 99 sheets of A4 size printing paper (100 sheets printed in total). In the intermittent printing, a cycle of printing for 4.3 seconds and pausing printing for about 0.5 seconds was repeated. After that, a second evaluation image consisting of only a blank image was printed on the printing paper.
[0180] Next, using the evaluation machine, a pattern image (character pattern image) with a print rate of 1% was intermittently printed on 900 sheets of A4 size printing paper (1000 sheets printed in total). In the intermittent printing, a cycle of printing for 4.3 seconds and pausing printing for about 0.5 seconds was repeated. After that, a third evaluation image consisting of only a blank image was printed on the printing paper.
[0181] Next, using the evaluation machine, solid images were continuously printed on 100 sheets of A4 size printing paper at a printing rate of 50% (1100 sheets printed in total). After that, a fourth evaluation image consisting of only a blank image was printed on the printing paper.
[0182] Using a white light meter (Tokyo Denshoku Co., Ltd. "TC-6DS"), the reflection density X1 of the first evaluation image and the reflection density X of the second evaluation image were measured. 100 and the reflection density X of the third evaluation image 1000 and the reflection density of the blank printing paper X BG The fog density of the first evaluation image (FD1) and the fog density of the second evaluation image (FD 100 ), fog density of the third evaluation image (FD 1000 ) and the fog density of the fourth evaluation image (FD 1100 The fogging of each developer was evaluated according to the following criteria. FD1=Reflection density X1-Reflection density X BG FD 100 = reflection density X 100 -Reflection density BG FD 1000 = reflection density X 1000 -Reflection density BG FD 1100 = reflection density X 1100 -Reflection density BG
[0183] (Fog standard) A (good): FD1, FD 100 , F.D. 1000 and FD 1100 All of the following are less than 0.010. B (bad): FD1, FD 100 , F.D. 1000 and FD 1100 At least one of these is 0.011 or greater.
[0184] [Table 5]
[0185] As shown in Tables 1 to 5, the number average primary particle diameters of the first strontium titanate particles and the second strontium titanate particles of the developers (D-1) to (D-2), (D-4), (D-7) to (D-8), (D-11) to (D-12), (D-14) to (D-15), (D-17) to (D-18), (D-21) to (D-22), and (D-26) to (D-27) were 15 nm or more and 85 nm or less, respectively. In addition, in each of the above-mentioned developers, the difference in the number average primary particle diameters of the first strontium titanate particles and the second strontium titanate particles was 10 nm or less. Furthermore, in each of the above-mentioned developers, the content of the second strontium titanate particles relative to 100.0 parts by mass of the toner mother particles was 0.3 parts by mass or more and 0.9 parts by mass or less. Furthermore, in each of the above-mentioned developers, the content of barium titanate particles per 100 parts by mass of the coating resin was 2 parts by mass or more and 47 parts by mass or less. Furthermore, in each of the above-mentioned developers, the content of strontium titanate first particles per 100.00 parts by mass of the carrier mother particles was 0.02 parts by mass or more and 0.06 parts by mass or less. Furthermore, in each of the above-mentioned developers, the ratio (N / L) satisfied formula (1). Each of the above-mentioned developers was able to suppress the occurrence of fogging.
[0186] On the other hand, fogging occurred in the developers (D-3), (D-5) to (D-6), (D-9) to (D-10), (D-13), (D-16), (D-19) to (D-20), and (D-23) to (D-25). The reason is presumed to be as follows.
[0187] The content of strontium titanate particles in the carrier particles of developer (D-3) was insufficient. As a result, it is determined that the charge rise of the toner contained in the replenishment developer of developer (D-3) was slow. Conversely, the content of strontium titanate particles in the carrier particles of developer (D-5) was excessive. As a result, it is determined that the toner of developer (D-5) had an insufficient charge due to insufficient contact between the silicone resin, which is the charge generation source, and the toner.
[0188] Furthermore, the content of strontium titanate particles in the toner particles of developer (D-6) was insufficient. It is determined that the charge amount of the toner in developer (D-6) was unstable. Conversely, the content of strontium titanate particles in the toner particles of developer (D-9) was excessive. In developer (D-9), the strontium titanate particles that were not retained on the toner surface hindered contact between the toner particles and the carrier particles. As a result, it is determined that the toner in developer (D-9) was insufficiently charged.
[0189] In the developer (D-10), the strontium titanate particles in the toner were rapidly detached from the toner from the early stage of the printing test. As a result, the ratio (N / L) of the developer (D-10) did not satisfy formula (1) at least at time t1.
[0190] In the developer (D-13), the strontium titanate particles in the carrier were rapidly detached from the carrier from the early stage of the printing test. As a result, the ratio (N / L) of the developer (D-13) did not satisfy formula (1) at least at time t1.
[0191] The content of barium titanate particles in the coating layer of the carrier particles in the developer (D-16) was insufficient. As a result, it is believed that the electrostatic capacity of the carrier in the developer (D-16) was small, resulting in large fluctuations in the amount of charge of the toner.
[0192] The developer (D-19) had an excessive content of barium titanate particles in the coating layer of the carrier particles, and it was therefore determined that the toner in the developer (D-19) had a poor charging property.
[0193] In developer (D-20), the size of the strontium titanate particles and the strontium titanate particles were too small. As a result, it is judged that developer (D-20) had difficulty in transferring charge between the toner particles and the carrier particles, and the charge rise property of the toner was poor. Conversely, developer (D-23) had the size of the strontium titanate particles and the strontium titanate particles that were too large. As a result, it is judged that developer (D-23) had the strontium titanate particles and the strontium titanate particles that rapidly detached from the early stage of printing.
[0194] In the developers (D-24) and (D-25), the difference in the number average primary particle diameter between the strontium first titanate particles and the strontium second titanate particles was excessive. As a result, it is judged that the developers (D-24) and (D-25) caused the detachment of the strontium first titanate particles and the strontium second titanate particles and the toner charging failure. [Industrial Applicability]
[0195] The two-component developer and image forming apparatus of the present invention can be used to form images in, for example, a copier, a printer, or a multifunction machine. [Explanation of symbols]
[0196] 1. Carrier particles 2. Carrier mother particles 2a Career Core 2b Coating layer 3 Strontium titanate particles 4 Toner particles 5 Toner base particles 6 External additives 6a Strontium titanate particles 6b Base Silica Particles 6c Spacer particles 40 Image forming device 41 Photoreceptor 42 Charging device 44 Developing device
Claims
1. A carrier including carrier particles and a toner including toner particles, the carrier particles have carrier base particles and strontium titanate particles attached to the surfaces of the carrier base particles, The carrier base particle has a carrier core and a coating layer that covers the carrier core, The coating layer contains a coating resin and barium titanate particles, The coating resin includes a silicone resin, The toner particles include toner base particles and an external additive attached to a surface of the toner base particles, The external additive contains strontium titanate particles, the number average primary particle diameter of the strontium titanate particles and the strontium titanate particles is 15 nm or more and 85 nm or less, a difference in number average primary particle size between the first strontium titanate particles and the second strontium titanate particles is 10 nm or less; the content of the strontium titanate particles is 0.3 parts by mass or more and 0.9 parts by mass or less with respect to 100.0 parts by mass of the toner base particles, The content of the barium titanate particles relative to 100 parts by mass of the coating resin is 2 parts by mass or more and 47 parts by mass or less, the content of the strontium titanate first particles is 0.02 parts by mass or more and 0.06 parts by mass or less relative to 100.00 parts by mass of the carrier base particles, When a printing test was conducted in which a pattern image with a print rate of 1% was printed intermittently on A4 size printing paper, Immediately after printing the first page, t 1 , and immediately after printing the 100th sheet, time t 100 , and immediately after printing the 1000th sheet, t 1000 a ratio (N / L) of a detachment rate N of the first strontium titanate particles to a detachment rate L of the second strontium titanate particles at any time satisfies the following formula (1): 1.1≦N / L≦6.5 (1) (The detachment rate N is the content of the first strontium titanate particles in the carrier particles before the printing test P 1 The content of the first strontium titanate particles immediately after printing a predetermined number of sheets is Q 1 Then, N = 100 × (P 1 -Q 1 ) / P 1 It is calculated as The detachment rate L is the content of the strontium titanate particles in the toner particles before the printing test. 2 The content of the strontium titanate particles immediately after printing a predetermined number of sheets is Q 2 Then, L = 100 × (P 2 -Q 2 ) / P 2 It is calculated as follows.)
2. The two-component developer according to claim 1 , wherein the coating layer further contains carbon black.
3. 3. The two-component developer according to claim 2, wherein the content of the carbon black relative to 100 parts by mass of the coating resin is 3 parts by mass or more and 20 parts by mass or less.
4. 3. The two-component developer according to claim 1, wherein the barium titanate particles have a number average primary particle diameter of 100 nm or more and 500 nm or less.
5. The external additive further includes spacer particles, The two-component developer according to claim 1 or 2, wherein the number average primary particle diameter of the spacer particles is 35 nm or more and 200 nm or less.
6. The two-component developer according to claim 1 or 2, which is an initial developer for use in an image forming apparatus of a trickle development system.
7. The two-component developer according to claim 1 or 2, A photoconductor; a charging device for charging the surface of the photoreceptor; a developing device that supplies the toner to a surface of the photoconductor and develops the toner image, The printing test is performed using the image forming apparatus.
Citation Information
Patent Citations
Carrier for electrophotographic developer, developer and process cartridge
JP2005091878A